Thrombotic microangiopathy after kidney transplantation: Analysis of the Brazilian Atypical Hemolytic Uremic Syndrome cohort - Nga, Hong Si [UNESP]; Palma, Lilian Monteiro Pereira; Neto, Miguel Ernandes [UNESP]; Fernandes-Charpiot, Ida Maria Maximina; Garcia, Valter Duro; Kist, Roger; Miranda, Silvana Maria Carvalho; de Souza, Pedro Augusto Macedo; Pereira, Gerson Marques; De Andrade, Luis Gustavo Modelli [UNESP] (Public Library of Science (PLoS), 2021)
Background Atypical Hemolytic Uremic Syndrome (aHUS) is an ultra-rare disease that potentially leads to kidney graft failure due to ongoing Thrombotic Microangiopathy (TMA). The aim was evaluating the frequency of TMA after kidney transplantation in patients with aHUS in a Brazilian cohort stratified by the use of the specific complement-inhibitor eculizumab. Methods This was a multicenter retrospective cohort study including kidney transplant patients diagnosed with aHUS. We collected data from 118 transplant centers in Brazil concerning aHUS transplanted patients between 01/01/2007 and 12/31/2019. Patients were stratified into three groups: no use of eculizumab (No Eculizumab Group), use of eculizumab for treatment of after transplantation TMA (Therapeutic Group), and use of eculizumab for prophylaxis of aHUS recurrence (Prophylactic Group). Results Thirty-eight patients with aHUS who received kidney transplantation were enrolled in the study. Patients' mean age was 30 years (24-40), and the majority of participants was women (63% of cases). In the No Eculizumab Group (n = 11), there was a 91% graft loss due to the TMA. The hazard ratio of TMA graft loss was 0.07 [0.01-0.55], p = 0.012 in the eculizumab Prophylactic Group and 0.04 [0.00-0.28], p = 0.002 in the eculizumab Therapeutic Group. Conclusion The TMA graft loss in the absence of a specific complement-inhibitor was higher among the Brazilian cohort of kidney transplant patients. This finding reinforces the need of eculizumab use for treatment of aHUS kidney transplant patients. Cost optimization analysis and the early access to C5 inhibitors are suggested, especially in low-medium income countries.